Communicating the Crisis: Study on the Local Government's Twitter Accounts During the Covid-19 Pandemic in Indonesia - Farisha Sestri Musdalifah; Annada Nasyaya; Anang Dwi Santoso (ULTIMA Comm, 2023)
Along with the increasing number of victims of COVID-19, the amount of information requested by the public on social media also continues to increase. The emergence of various hoaxes that can influence individual behavior is also an urgent reason for the government to come and contribute. Although the urgency of the government's presence on social media at the time of the COVID-19 pandemic has been recognized, not many studies have looked at this presence, especially whether their presence is beneficial. For this reason, the goal to be achieved in this research is whether local governments provide sufficient and appropriate information required by the Indonesian during the pandemic. This study analyzes the Twitter accounts of local governments in Indonesia that have implemented Large-Scale Social Restrictions (PSBB) by taking tweets for content analysis and replies, retweets, and likes, to see the stakeholder engagement index (SEI). The results of this study indicate that information about reporting on the situation is the content most commonly shared by local governments through their Twitter accounts. The findings also show that the Tangerang Regency Government Twitter account has the highest Stakeholder Engagement Index, indicating the high level of public participation in information shared by the government through Twitter social media accounts. Academically this research fills the gaps between communication streams in crises by providing the need for and availability of information that, in practical terms, can be used to guide the creation of social media content during a pandemic.